The Relationship Between Breakfast Habits and Playing Activities for Children Aged 5-6 Years in Al-Kautsar Integrated Islamic Kindergarten - Lisda, Kurnia; Mahyuddin, Nenny (EduBasic Journal: Jurnal Pendidikan Dasar, 2023)
Breakfast is essential since it affects children's playing activities at school. This study, therefore, aimed to determine the relationship between breakfast habits and children's playing activities aged 5-6 years at Al-Kautsar Integrated Islamic Kindergarten, Lubuk Begalung, Padang. The research approach used was quantitative with this type of correlational research. The sample studied was 41 children. Data collection techniques employed observation and questionnaires. The instrument utilized was an observation sheet of children's breakfast habits filled in by the child's parents, while the teacher filled in a questionnaire about playing activities. The instrument was tested for validity and reliability. Testing the instrument validity used the Product Moment formula, whereas the reliability test used was the Alpha formula. The data analysis technique used was a product-moment correlation for hypothesis testing. The results of testing the hypothesis in this study obtained an R-count of 0.527. This result was more significant than the r-table at a significance level of 5%, gained 0.316. This study found a positive relationship between breakfast habits and playing activities of children aged 5-6 years at Al-Kautsar Integrated Islamic Kindergarten, Lubuk Begalung, Padang. The effective contribution of breakfast habits to playing activities in children aged 5-6 years at Al-Kautsar Islamic Integrated Kindergarten, Lubuk Begalung, Padang, was r2 x 100%, i.e., 27.75%. This result could be a reference for parents and teachers to be more concerned about breakfast habits for children's development.